An efficient method for production of kynurenic acid by Yarrowia lipolytica. Issue 9 (8th May 2020) - Wróbel‐Kwiatkowska, Magdalena; Turski, Waldemar; Kocki, Tomasz; Rakicka‐Pustułka, Magdalena; Rymowicz, Waldemar
Abstract: Kynurenic acid (KYNA) is a compound derived from the tryptophan catabolic pathway. Antioxidant and neuroprotective properties have been confirmed for KYNA, which makes it an interesting and important metabolite of biomedical significance. In the present study, the yeast Yarrowia lipolytica was tested for KYNA biosynthesis. The results showed that Y. lipolytica strain S12 is able to produce KYNA in high concentrations (up to 21.38 μg/ml in culture broth and 494.16 μg/g cell dry weight in biomass) in optimized conditions in a medium supplemented with tryptophan. Different conditions of culture growth, including the source of carbon, its concentration and pH value of the medium, as well as the influence of an inhibitor or precursor of KYNA synthesis, were analysed. The obtained data confirmed the presence of KYNA metabolic pathway in the investigated yeast. To our best knowledge, this is the first study that reports KYNA production in the yeast Y. lipolytica in submerged fermentation.